Characteristics of pitting corrosion in an existing reinforced concrete beam exposed to marine environment. (20th February 2020) - Zhao, Yuxi; Xu, Xiaoyi; Wang, Yuzhou; Dong, Jianfeng
Highlights: Corrosion pits are located next to the defects in concrete. There are two types of pits: wide-shallow pit and narrow-deep pit. An ellipse model is proposed to describe the shape of corrosion pits. The growth trends of the wide-shallow pit and the narrow-deep pit are opposite. The pitting factors are different between the wide-shallow and narrow-deep pit. Abstract: Pitting corrosion is a threat to structural durability, causing stress concentration and severe effects on bearing capacity. In this study, two types of corrosion pits were observed in an existing beam exposed to a marine environment for forty years: a wide-shallow pit and narrow-deep pit. Considering the pitting corrosion depth and width as key parameters, an ellipse model was proposed to describe the pit shape. The ratio between the maximum and the average corrosion penetration, called pitting factor, was found to fluctuate between 2 and 4 for the wide-shallow pit and between 4 and 8 for the narrow-deep pit.